Workshop and Assistance on the Utilization of E-Learning at the Universitas Muhammadiyah Buton - Iksan, Muhamad; Alzarliani, Wa Ode; Samritin, Samritin; Azaluddin, Azaluddin; Awaluddin, Muhammad (Edumedia Solution, 2023)
Improving the learning system chosen by the Universitas Muhammadiyah Buton (UM Buton) in order to compete in the era of disruption with advances in information and communication technology (ICT), particularly electronic-based learning systems, one of which is known as the e-learning learning system. Several professors at UM Buton had difficulties in adding learning material in the form of text, and video, visualizing quiz results and semester examinations, and building forums for question-and-answer sessions while utilizing e-learning. Based on these issues, the service team developed training and mentoring for UM Buton lecturers. It is hoped that with this training, UM Buton will be able to produce quality lecturers and highly educated skilled professionals who can keep up with the times and ICT-based technology while carrying out Catur Dharma tasks and responsibilities as a lecturer at Muhammadiyah Higher Education.